2019
DOI: 10.9778/cmajo.20180099
|View full text |Cite
|
Sign up to set email alerts
|

Social licence and the general public’s attitudes toward research based on linked administrative health data: a qualitative study

Abstract: round the world, specialized research centres have developed expertise related to the linkage and analysis of population-wide administrative health data. 1 Canadian examples include ICES in Ontario, 2 the Manitoba Centre for Health Policy, 3 Population Data BC 4 and the Canadian Institute for Health Information. 5 These organizations all work with data sets that are created by linking person-level data from different data sets (e.g., prescription drugs, hospital admissions, mortality) then removing or coding i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
60
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 13 publications
8
60
0
2
Order By: Relevance
“…Even before the era of big data, people described concerns about the use of health data for research, particularly as the data are made available to more individuals and groups. Paprica and colleagues 12 recently conducted a focus group on the use of health data with Canadian stakeholders and identified a strong suspicion of private industry, which had been noted by other investigators. 7,10,11 Similarly, Ethical concerns around use of artificial intelligence in health care research from the perspective of patients with meningioma, caregivers and health care providers: a qualitative study Research Kim and colleagues 13 discovered that it is important to patients whom their health information and biospecimens are shared with for research purposes; particular hesitance was observed in sharing data with for-profit institutions.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Even before the era of big data, people described concerns about the use of health data for research, particularly as the data are made available to more individuals and groups. Paprica and colleagues 12 recently conducted a focus group on the use of health data with Canadian stakeholders and identified a strong suspicion of private industry, which had been noted by other investigators. 7,10,11 Similarly, Ethical concerns around use of artificial intelligence in health care research from the perspective of patients with meningioma, caregivers and health care providers: a qualitative study Research Kim and colleagues 13 discovered that it is important to patients whom their health information and biospecimens are shared with for research purposes; particular hesitance was observed in sharing data with for-profit institutions.…”
mentioning
confidence: 90%
“…However, the speed of progress and potential for benefit of the technology are are mired by ethical controversies surrounding the use of AI more broadly that may undermine public trust in this technology. 4 Public perceptions regarding health data use for research are well characterized, [5][6][7][8][9][10][11][12][13] but limited work specific to public perceptions of AI has been noted. [14][15][16] Consistently across the globe, members of the public value the benefit to be gained from medical research but are concerned about the privacy of personal health data.…”
mentioning
confidence: 99%
“…One tension inherent in the use of linked data for research is that there is both the potential to benefit society and some level of risk to privacy, security, and of unethical behaviour toward individuals represented in the data [5]. As the Nuffield Council on Bioethics notes, the "public interest" includes both supporting responsible use of data and protecting the privacy of individuals [6], and recent public engagements suggest the public does in fact hold quite nuanced views on data sharing [7,8]. These engagements illustrate that the public is not automatically for or against issues such as sharing of data or the involvement of the private sector, but instead focuses on the context, including considerations such as who is asking, for what, to be used for what purpose [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…We believe that achieving effective proportionate governance of health data [19] requires authentic public and patient involvement that follows accepted principles such as inclusiveness, two-way communication and transparency [20]. There is a growing body of research evidence about public expectations around social licence and acceptable data uses of health data [21][22][23][24], and increasing commitment from many institutions to include the public in one way or another to inform or influence policies [7][8][9][10], but we have not yet implemented or operationalized the principles and ideas presented in the research literature at scale. One approach, presented here, is to create some standardized communications that distinguish between different uses of health data to ensure that members of the public do not confuse, or group together, commercial revenue-generating uses with public sector data-intensive health research.…”
mentioning
confidence: 99%
“…The international research literature describes general but conditional public support for dataintensive health research. Qualitative studies indicate that members of the public view health data as an asset that should be used as long as there is a public benefit and their concerns related to privacy, commercial motives and other risks are addressed [21][22][23][24]. The Wellcome Trust, Ipsos Mori One-Way Mirror Report identifies four 'key tests' for public acceptability of commercial use of health data [24]:…”
mentioning
confidence: 99%